On intuitionistic Fuzzy Asly Ideal of Ring - E., Showq Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper we tend to describe the notions of intuitionistic fuzzy asly ideal of ring indicated by (I. F.ASLY) ideal and, we will explore some properties and connections about this concept.